Distribution of SNPs based on CG/CG to TG/CA Mutation in Different Regions of Human Genome - Kumari, Arash (My University, 2012)
Methylated cytosines undergo spontaneous deamination leading to its conversion into thymine placed opposite to guanine in the complementary strand. If the mismatch is not repaired before replication it generates mutation. CpG mutation is one of the contributory factors that have generated SNPs in human genome 22. In present study we have investigated the correlation between methylation level at flanks of CG-SNP (based on CG/CG to TG/CA) and the allele frequencies of these SNP across the human genome. Further we have investigated the distribution of CG-SNP in different genomic regions such as exons, introns, 5‘ UTR and 3‘ UTR to study the effect of evolutionary pressure on changes in sequences using SNPs as tools. Also, we have determined flanking sequences of up to ±4 base pairs surrounding the central CG-SNP sites that show characteristic high and low allele frequencies in human genome.
Master of Science (Biotechnology)
Keywords: SNP; mutation; human; Genome